Vitamin D and Skin: An Review and Update - Aryal, Eliz; Bhari, Jyoti (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Vitamin D was recognized for its pivotal role in bone formation, but it is now recognized for its impact on the optimal functioning of various tissues throughout the body, including the brain, heart, muscles, immune system, and skin. Vitamin D is a fat-soluble prohormone steroid with endocrine, paracrine, and autocrine functions. Vitamin D receptors and the enzymes that can convert 25-hydroxyvitamin D [25(OH)D] into the active form, 1,25-hydroxyvitamin D [1,25(OH)D], have been identified in numerous cells throughout the body, including the skin. Vitamin D analogs are widely acknowledged for effective treatment of psoriasis vulgaris due to their anti-proliferative and pro-differentiating impact on keratinocytes. Beyond this, emerging roles for vitamin D in skin health include immunomodulatory and anti-apoptotic effects, suggesting potential applications in conditions like atopic dermatitis and infections including verucca vulgaris. Epidemiological studies have linked low vitamin D levels to autoimmune diseases like vitiligo, leading to the use of topical vitamin D in its treatment. Recent evidence also suggests that cutaneous vitamin D synthesis may contribute to preventing skin malignancies, and oral supplementation may reduce cancer mortality. Its role in the pathogenesis of various dermatological diseases has not been an exception and has been extensively studied in recent years. In this review, we will shed light on roles of vitamin D in various skin disorders.